Three new species of the Neotropical genus Protoconnus Franz (Coleoptera: Staphylinidae: Scydmaeninae) - Jałoszyński, Paweł (Zootaxa, 2020)
Protoconnus Franz currently comprises 25 nominal species distributed in Bolivia, Costa Rica, Ecuador, Panama, Paraguay, Peru, and Venezuela. Three new species are described: P. fenestratus sp. n. (Peru), P. brachati sp. n. (Venezuela), and P. carabobonus sp. n. (Venezuela). New species are illustrated, and their characters shared with previously described congeners are discussed.